Resurrection of the enigmatic species Prangos akymatodes (Apiaceae) from Central Afghanistan - Lyskov, Dmitry; Samigullin, Tahir (Phytotaxa, 2017)
Based on molecular and morphological evidence, the narrow endemic to Afghanistan Prangos akymatodes has been re-established from synonymy under P. uloptera. The main diagnostic characters (shape and length of leaf lobes, shape of fruits and wings of mericarps) are different in the two species. Molecular analysis of nrITS/ETS markers supported P. akymatodes as a distinct species and placed it in the subgenus Koelzella, the species of which are mostly distributed in the Tien Shan Mountains.